Activities for Fostering Disability Awareness and Friendship in Inclusive School - Ossy Firstanti Wardany; Wagimin; M. Furqon Hidayatullah (Indonesian Journal of Disability Studies, 2018)
Fostering disability awareness is important to improve peer acceptance and friendship between students with special needs and regular students. This study is a narrative review of previous research on activity for fostering disability awareness. We reviewed 16 studies that fit the criteria that we found on E-resources National Library of Indonesia. We find some activity to build awareness, namely, reading books about disability, peer network strategy, thematic intervention, puppets show, drawing comics, simulation, play intervention and sports activities. These activities can be references for teachers to improve acceptance and friendship in inclusive schools.